Are Weak Banks Leading Credit Booms? : Evidence from Emerging Europe - Igan, Deniz (IMF Working Papers; Working Paper ;, 2008)
This paper examines the behavior of bank soundness indicators during episodes of brisk loan growth, using bank-level data for central and eastern Europe and controlling for the feedback effect of credit growth on bank soundness. No evidence is found that rapid loan expansion has weakened banks during the last decade, but over time weaker banks seem to have started to expand at least as fast as, and in some markets faster than, stronger banks. These findings suggest that during credit booms supervisors need to carefully monitor the soundness of rapidly expanding banks and stand ready to take action to limit the expansion of weak banks.